Correlation Between Accompanying Symptoms of Facial Nerve Palsy, Clinical Assessment Scales and Surface Electromyography - Gyu Hui Kim; Jung Hyeon Park; Tae Kyung Kim; Eun Ju Lee; Su Eun Jung; Jong Cheol Seo; Cheol Hong Kim; Yoo Min Choi; Hyun Min Yoon (MEDrang Inc., 2022)
Background This retrospective study aimed to determine whether there were correlations between the number and type of accompanying symptoms of peripheral facial nerve palsy, and surface electromyography (SEMG) and clinical assessment scales to help diagnosis. Methods There were 30, cases of peripheral facial nerve palsy at Visit 1 to the Korean Medicine Hospital, Dong-eui University, 22 cases at Visit 2 and 10 cases at Visit 3. The study period was from July 19, 2021 to November 31, 2021. Symptoms were evaluated three times (with two-week intervals which began 7 days from onset) using SEMG, clinical assessment scales and accompanying symptoms. In this study, the House-Brackmann grading system (HBGS), and the Yanagihara's unweighted grading system (Y-score) clinical assessment scales were used. The Pearson or Spearman correlation was used for statistical analysis. Results On Visit 1, the number of accompanying symptoms of peripheral facial nerve palsy had no significant correlation with other measures. On Visits 1-3, the HBGS score had a significant negative correlation with the Y-score. On Visit 2, most of the mean values measured had significant correlations with each other although not between SEMG-Z and SEMG-O that Z means a zygomaticus muscle and O means a orbicularis oris muscle. On Visit 3, the number of accompanying symptoms significantly correlated with the clinical assessment scales. The HBGS score, Y-score, and SEMG measurements (except SEMG-Z) had significant correlations with each other. A significant positive correlation between SEMG-Z and SEMG-T was noted. Conclusion We predict accompanying symptoms can be used to diagnose the peripheral facial nerve palsy including both clinical assessment scales and SEMG measurements at 2-5 weeks after onset.